Early Skin Toxicity as a Predictive Factor for Tumor Control in Hepatocellular Carcinoma Patients Treated with Sorafenib - Vincenzi, Bruno (AlphaMed Press, 2010)
INTRODUCTION. Sorafenib is an oral multikinase inhibitor that targets Raf kinase and receptor tyrosine kinases and has led to a longer median overall survival (OS) time and time to progression (TTP) in patients with advanced hepatocellular carcinoma (HCC). This study was conducted to assess the link between the antitumor efficacy of sorafenib and its early cutaneous side effects in advanced HCC patients. MATERIALS AND METHODS. All patients received 800 mg daily of sorafenib until progression or unacceptable toxicities. We retrospectively analyzed the incidence of rash and hand–foot skin reactions (HFSR) during the first month of treatment, comparing tumor control (partial response plus stable disease) and TTP. RESULTS. Sixty-five HCC patients treated with sorafenib were included in this analysis: 47 (73.3%) received sorafenib after failure of some local treatment, whereas 18 (27.7%) received it as first-line treatment. Twenty-nine patients developed at least grade 1 skin toxicity (rash, 13; HFSR, 16). In patients who developed skin toxicity, the tumor control rate was 48.3%, versus 19.4% in patients without cutaneous side effects. The median TTP was 8.1 months in the group of patients with skin toxicity versus 4.0 months in those without skin toxicity. This difference was also statistically significant on multivariate analysis. A borderline statistically significant difference was also observed in terms of OS in patients with early skin toxicity. CONCLUSIONS. Skin toxicity should be closely monitored in HCC patients treated with sorafenib in relation to its potential role as a surrogate marker of efficacy.